Interpretation and Reconstruction of Chinese Cultural Symbols in Cross-cultural Communication - Chen, Lunqiang (International Journal of Social Sciences and Public Administration, 2025)
This article mainly studies the interpretation and reconstruction of Chinese cultural symbols in cross-cultural communication. By summarizing relevant concepts, it elaborates on the existing forms of Chinese cultural symbols in cross-cultural communication. It analyzes the current status of Chinese cultural symbols recognized by the international community and their negative images, highlighting the necessity of their interpretation and reconstruction. On this basis, the article explores the manifestations of Chinese cultural symbols in cross-cultural communication from aspects such as content presentation form, language expression form, color application form, character design form, and image presentation form. Additionally, it analyzes the causes of interpretation biases of Chinese cultural symbols, including differences in cultural contexts and factors such as communication subjects and channels. Finally, it proposes policy recommendations for Chinas international cultural exchange, including establishing a cross-cultural communication context, building international communication platforms, and enhancing international communication capabilities. Through the implementation of these policies, it is possible to effectively improve the interpretation biases of Chinese cultural symbols in cross-cultural communication and enhance their international influence.